Influence of concentration, time and method of application of citric acid and sodium citrate in root conditioning. - Cavassim, Rodrigo [UNESP]; Leite, Fábio Renato Manzolli; Zandim-Barcelos, Daniela Leal [UNESP]; Dantas, Andréa Abi Rached [UNESP]; Rached, Ricardo Samih Georges Abi [UNESP]; Sampaio, José Eduardo Cezar [UNESP] (FapUNIFESP (SciELO), 2012)
The aim of this study was to establish the parameters of concentration, time and mode of application of citric acid and sodium citrate in relation to root conditioning. A total of 495 samples were obtained and equally distributed among 11 groups (5 for testing different concentrations of citric acid, 5 for testing different concentrations of sodium citrate and 1 control group). After laboratorial processing, the samples were analyzed under scanning electron microscopy. A previously calibrated and blind examiner evaluated micrographs of the samples. Non-parametric statistical analysis was performed to analyze the data obtained. Brushing 25% citric acid for 3 min, promoted greater exposure of collagen fibers in comparison with the brushing of 1% citric acid for 1 minute and its topical application at 1% for 3 min. Sodium citrate exposed collagen fibers in a few number of samples. Despite the lack of statistical significance, better results for collagen exposure were obtained with brushing application of 25% citric acid for 3 min than with other application parameter. Sodium citrate produced a few number of samples with collagen exposure, so it is not indicated for root conditioning.
Keywords: chelating agent; citrate sodium; citric acid; collagen; dental acid etching; dental surgery; drug effect; human; instrumentation; methodology; scanning electron microscopy; time; tooth root; Acid Etching, Dental; Chelating Agents; Citrates; Citric Acid; Collagen; Dental Cavity Preparation; Humans; Microscopy, Electron, Scanning; Smear Layer; Time Factors; Tooth Root